SFM-VA : one-layer fabric membrane for sports apparel - Muhammad Feroz Jamalullah (Nanyang Technological University, 2021)
An effort has been made to create a single-layer hybrid fabric membrane to reduce manufacturing cost, time, and weight without compromising required functional performances such as water resistance, breathability, and wind resistance. This creation also aims to overcome the drawbacks associated with conventional laminate/coated fabrics such as multiple processing steps, delamination, degradation, and reduction in breathability due to adhesive layer, etc. In this work, the plaited jersey fabric was developed using polyester filament yarn and nylon fusible yarn. To develop a uniform film on fabric surface, the developed sample underwent hot press to melt the nylon fusible yarn present in the fabric structure. The hot press processing parameters such as temperature, pressure and time were optimized using Box-Behnken design via Minitab 19 to obtain best functional properties of the developed fabric membrane. As a result, optimized values for the processing variables were determined as 120 °C, 30 seconds and 5 tons which yielded a fabric membrane with an air permeability of 66 cfm, water vapor permeability of 875.7 (g/(m2·24h)), and grade 5 resistance to surface wetting. In addition, developed fabric membrane shows stiffness, abrasion, and tearing resistance comparable to current commercially available fabrics such as Gore-Tex® and others. This development can be potentially applied as shell fabrics for winter jackets, sleeping bags, shoe uppers, lightweight wind resistance jackets etc.